2017
DOI: 10.1007/s00702-017-1690-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between cognitive impairment and urinary dysfunction in Parkinson’s disease

Abstract: Urinary dysfunction (UD) is a common non-motor feature of Parkinson's disease (PD), and might be secondary to neurodegeneration involving cortical and subcortical brain areas. The possible link between UD and cognitive deficits has never been examined in frontal cortex impairment, and is still not completely understood in PD. In the present study, 94 PD patients underwent a comprehensive motor, cognitive and non-motor assessment. It was shown that 55.3% of patients reported UD, of which 17% needed specific uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Bladder dysfunction has been linked to a variety of clinical PD-related symptoms, including cognition (Sakushima et al, 2016;Tkaczynska et al, 2017). On the contrary, a recent study found no association between PD-UU and cognitive impairment (Picillo et al, 2017) where the applied cognitive screening assessment did not provide insight into the domain-specific characterization of cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Bladder dysfunction has been linked to a variety of clinical PD-related symptoms, including cognition (Sakushima et al, 2016;Tkaczynska et al, 2017). On the contrary, a recent study found no association between PD-UU and cognitive impairment (Picillo et al, 2017) where the applied cognitive screening assessment did not provide insight into the domain-specific characterization of cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies used questionnaires that solely focused on memory, namely the Memory Assessment Clinical Questionnaire (MAC‐Q), The Forgetfulness Assessment Inventory (FAI) and the Cognitive Complaints Interview (CCI). Similarly, a few other studies only asked one question relating to memory.…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies, except for one, reported cognitive screening tests. Seventeen studies used the Mini Mental State Examination (MMSE) for assessment of global cognitive abilities, while seven studies used Montreal Cognitive Assessment (MoCA), which are the most commonly used screening tests for cognitive decline. The rest of the studies used the Mattis Dementia Rating Scale (MDRS), the Scales for Outcome in PD‐Cognition (SCOPA‐COG), Addenbrooke's Cognitive Examination‐Revised (ACE‐R), the Parkinson Neuropsychometric Dementia Assessment (PANDA) and the Clinical Dementia Rating Scale (CDR).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micturition is a complicated process controlled by the frontal lobe, basal ganglia, brainstem, spinal cord, and the other central autonomic networks [2, 3]. Some studies have found that LUT dysfunction can exacerbate the extent of cognitive dysfunction [4, 5] and might be an early sign of accelerating PD progression [6]. Therefore, discovering the relevant factors and using them to develop an early intervention strategy for LUT dysfunction in PD patients is of great importance.…”
Section: Introductionmentioning
confidence: 99%